The Growing Points of Studies in Informal Economy or Objectifying the Subjective. Book Review: Barsukova S. (2015) Essays on Informal Economy, or Sixteen Shades of Gray, Moscow: NRU HSE - KolesnikNatalya (Journal of Economic Sociology, 2016)
The economic development of Russian society during the post-Soviet period has interested not only economists and politicians but also sociologists. This interest explains the rise in sociological studies of informal economic practices and the intensive growth in this field of research in Russia over the last 20 years. “Essays on Informal Economy, or Sixteen Shades of Gray” by Professor Svetlana Barsukova of Moscow NRU HSE has supported previous studies. In her book, the author seeks answers to the following questions: What is specific about the informal economy in Russia? What characterizes the relations between business and government? What are the reasons for the expansion of the informal economy? Firstly, the author tries to show the reader how the informal economy is understood and analyzed by various authors in different books. Secondly, she puts forward her personal views on the phenomenon of the informal economy. The book can be read by anyone, even by those who have just started exploring economic sociology and economics.